Tafsir al-Qur’an Aksara Pegon dan Bahasa Jawa - Amrulloh, Tri Febriandi; Fachruddin, Zhafirah; Hakim, Muhammad Naufal; Amrullah, Abdul Karim (SUHUF, 2024)
This article examines one of the Javanese-Pegon Quranic exegeses emerging from the background of pesantren (Islamic boarding schools). The subject of this study is the Tafsir al-Mahalli li Ma‘rifati Ayati al-Qur’an wa Nuzuliha by Ahmad Mudjab Mahalli. Through the Gadamerian hermeneutic approach, this study demonstrates that the emergence of Tafsir al-Mahalli is a response to the local communities’ demand to study and understand the Quran without language difficulties. This tafsir also reflects Mudjab Mahalli’s academic concern in responding to previous exegeses that he deemed insufficient in contextualizing the Quran among the local community. In terms of appearance, the tafsir was written in Javanese language and pegon script, indicating the author’s close connection with pesantren culture. Furthermore, from the communicational aspect, Mudjab Mahalli preferred to use polite Javanese language (Jawa krama) in his delivery, making the conveyed message more accessible to the local community. Regarding his interpretation, Mudjab Mahalli appeared accommodating towards Javanese cultural forms of address, such as using honorifics like Paduka and Pangeran. Moreover, the hierarchy of the Javanese language employed in his tafsir indicates the Mufassir’s careful consideration of linguistic etiquette. These local elements were shaped by Mudjab Mahalli’s interaction with religious values present in the pesantren environment.